Sex and age differences in habitat use by invasive cane toads (Rhinella marina) and a native anuran (Cyclorana australis) in the Australian wet–dry tropics. (19th August 2015) - González‐Bernal, Edna; Brown, Gregory P.; Crowther, Mathew S.; Shine, Richard
Abstract: Although generalized habitat use may contribute to the success of invasive taxa, even species that are typically described as habitat generalists exhibit non‐random patterns of habitat use. We measured abiotic and biotic factors in 42 plots (each 100 × 10 m) along a 4.2‐km long unpaved road in tropical Australia, at a site that had been invaded by cane toads ( R hinella marina  Bufonidae) seven years previously. We also counted anurans at night in each of these plots on 103 nights during the tropical wet season, over a five‐year period, beginning soon after the initial toad invasion. Spatial distributions differed significantly among adult male toads ( n  = 1047), adult female toads ( n  = 1222), juvenile toads ( n  = 342) and native frogs ( C yclorana australis  Hylidae, n  = 234). Adult male toads were closely associated with water bodies used as calling and/or spawning sites, whereas adult female toads and native frogs were most commonly encountered in drier forested areas on sloping ground. Juvenile toads used the margins of the floodplain more than conspecific adults did, but the floodplain itself was rarely used. Understanding which components of the habitat are most important to specific age and sex classes within a population, or how invasive species differ from native species in this respect, can clarify issues such as the spatial and temporal location of ecological impact by an invader, and the most effective places for control of the invader with minimal collateral effects on the native biota.